MelanoDet: Multimodal Imaging System for Screening and Analysis of Cutaneous Melanoma - Alina Elena Sultana; Maria Oniga; Paul Florin Rus; Andra Laura Dobre; Olguta Anca Orzan (IEEE Access)
Cutaneous melanoma is one of the most aggressive skin cancers, and early detection is critical for effective treatment. Although traditional imaging techniques such as dermoscopy improve diagnostic accuracy, many cases remain undetected. Recent advancements in non-invasive imaging, including multispectral imaging and infrared thermal imaging, offer new opportunities for early diagnosis. In this study, we introduce MelanoDet, a multimodal imaging system integrating three cameras corresponding to different spectra: visible, near-infrared, and long-wavelength infrared. To ensure accurate lesion inspection, an analytical method based on the optical cameras parameters estimated the cameras’ common field of view, to capture the same region of interest. Since the acquired images differ in resolution, angle, and orientation, a second refined registration step has been applied. A standardized image acquisition protocol was established in collaboration with an experienced team of dermatologists from Elias Emergency University Hospital, Bucharest. The MelanoDet system, along with its protocol and image processing techniques, was validated on 25 cases of suspicious nevi, demonstrating its potential for improving melanoma screening.